PERSEPSI PESERTA DIDIK TENTANG PENTINGNYA BELAJAR BAHASA JERMAN DI ERA GLOBALISASI - Ida Costansa Tamaela; Eldaa Crystle Wenno; Piet Soumokil (Universitas Pattimura, 2022)
The purpose of this virtual outreach activities at SMAN 4 Masohi, Central Maluku district, with the theme